Protein for Human Consumption From Oilseed Cakes: A Review - Singh, Renu; Langyan, Sapna; Sangwan, Seema; Rohtagi, Bharti; Khandelwal, Ashish; Shrivastava, Manoj (Frontiers in Sustainable Food Systems, 2022)
Oilseed cakes left after the oil extraction for different purposes are chiefly used as cattle feed, compost amendment, or plant conditioner. These oilseed cakes are rich in protein, nitrogenous compounds, and minerals. Beside its conventional usage, studies have been conducted to utilize these protein rich resource for human consumption. Considering the exponentially increasing human population and escalating food prices, these protein rich sources can be a novel food commodity and used to extract protein. The quality and functional properties of extracted oilseed cake proteins not only supplement the existing protein sources for the human consumption but also solve the problem of oilseed cakes disposal along with the additional income to the oilseed crop producers and processers. Production of proteins for human consumption from oil seed cakes may also reduce the carbon and water footprints while producing animal protein. The present review will focused on analysing the oilseed cake as a protein source, characterization, extraction techniques, and utilization in food products